Пам’ять, історична проза та формування національної ідентичності - Набитович, І. (Слово і Час, 2022)
У статті на прикладі історичної прози української еміграції розглянуто,
як взаємні проєкції пам’яті й історичної художньої епіки впливають на
становлення національної самосвідомості та ідентичності. Власне ця
проза еміграції як вигнання свідчить про появу і взаємопроникнення головних ідей і концептів, естетичної, образної парадигми, що формуються на
пограниччі пам’яті, історії і красного письменства. Саме в такому ракурсі висвітлено історичну прозу як цілеспрямовану політику пам’яті. Ця література витворює у контексті конструювання основ національної ідентичності, крім іншого (через пошук закорінення в минулому), тривкий системний ефект національного самоусвідомлення, етнічної самоідентифікації. Historical prose as a component of national literature is an essential part of the cultural life
of modern nations. One of its tasks is to form the cultural memory of large groups that create
national communities, structure the past and preserve its integrity and uniqueness.
The historical prose of Ukrainian emigration eloquently demonstrates mutual projections
of memory and the formation of national conscience and identity. The prose of emigration
as an exile can serve as a relief and expressive evidence of the formation and interpenetration
of the main ideas and concepts, ideological and aesthetic figurative paradigm,
formed on the border of memory, history, and literature. Th is is how historical prose is seen
as a purposeful policy of memory.
For societies where the state tradition was interrupted, historical prose can be considered
an important factor in restoring/maintaining national memory, as well as a means of
creating national myths, projecting the past on the modern problems of a stateless nation,
and preserving the national traditions.
Historical prose of Ukrainian emigration had these tasks in mind, taking responsibility
for the national philosophical perspective rooted in the past in order to preserve and
increase it in the future. The idea of self-discovery through one’s own history is, in particular,
an important element in the existence of Ukrainian emigration: in this case, we talk about
national self-knowledge in a community that tries to preserve its national identity and fix it
not only in oral tradition but also in scholarly historical research and historical prose.
Historical fiction of the 20th-century Ukrainian emigration was a means of discovering
the sources of traditions in the past that directly influences modernity, and an attempt to
build a historiosophical literary model that would reveal the forgotten past, show the causes
of current problems, and point out the way to future.